2017
DOI: 10.1109/mmul.2017.265090754
|View full text |Cite
|
Sign up to set email alerts
|

Biometrics: In Search of Identity and Security (Q & A)

Abstract: Abstract-To address the issues like identity theft and security threats, a continuously evolving technology known as biometrics is presently being deployed in a wide range of personal, government, and commercial applications. Despite the great progress in the field, several exigent problems have yet to be addressed to unleash biometrics full potential. This article aims to present an overview of biometric research and more importantly the significant progress that has been attained over the recent years. The p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 19 publications
1
16
0
Order By: Relevance
“…Note that the performances reported here are similar to some state-of-the-art results reported using the LFW+ 4 . For example, in [16] they reported mean average error of 7.8% for age and 94% and 90% of accuracy for gender and ethnicity, respectively.…”
Section: B Automatic Estimationsupporting
confidence: 86%
See 1 more Smart Citation
“…Note that the performances reported here are similar to some state-of-the-art results reported using the LFW+ 4 . For example, in [16] they reported mean average error of 7.8% for age and 94% and 90% of accuracy for gender and ethnicity, respectively.…”
Section: B Automatic Estimationsupporting
confidence: 86%
“…Soft biometrics refer to physical and behavioral traits that can be semantically described by humans [9], [19]. Although soft biometric traits may not possess sufficient distinctiveness or uniqueness to allow highly accurate recognition [4], they can be useful to enhance person recognition under certain conditions. For instance, Dantcheva et al [10] suggested that it might be possible to perform recognition when considering a sufficient number of them, in a bag of soft biometrics.…”
Section: Introductionmentioning
confidence: 99%
“…In other words, each FR system in this study is highly effective at detecting ZEI attacks, but is less than 10 times as effective in detecting PAs based on custom silicone masks. FR systems with IAPMR to FMR ratio > 10 are graded as highly vulnerable [3].…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, most common biometric modalities adopted are fingerprint and face [3], which are also considered in this work. The fingerprint matching algorithms can be categorised into three categories [1]:…”
Section: Biometric Modality Analysis (Matching)mentioning
confidence: 99%